Forecasting Seizure Freedom After Epilepsy Surgery Assessing Concordance Between Noninvasive and StereoEEG Findings. (18th November 2021) - Martin, Reinaldo Uribe San; Di Giacomo, Roberta; Mai, Roberto; Gozzo, Francesca; Pelliccia, Veronica; Mariani, Valeria; Cardinale, Francesco; Ciampi, Ethel; Onofrj, Marco; Tassi, Laura
Graphical Abstract: